2019
DOI: 10.2174/1871530319666190101124751
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Implication of FTO rs17817449 Gene Polymorphism on BMI Mediated Risk For Type2 Diabetes Among Obese Egyptian Children And Adolescents

Abstract: Background: Genetic variations of the FTO gene were associated with obesity and type 2 diabetes determinants in the European population, notably raised blood levels of insulin and glucose. Objective: The aim of this study was to test the association of FTOrs17817449 with obesity/BMI and type 2 diabetes risk among obese Egyptian population. Materials and Methods: In this case-control study, (PCR-RFLP assay) was used for genotyping FTOrs17817449polymorphism (SNP) in 120 obese children and 120 controls condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Surprisingly, some FTO associations had lower GGT values, thus indicating a protective role in liver enzyme concentrations. These included GG homozygosity which is a risk factor for obesity (Barseem et al, 2019;Hinney et al, 2007;Jawad & Rasool, 2019;Scuteri et al, 2007) and T2DM development (Hubacek et al, 2018. We are also aware of only one study which associated risk with the T allele. Therein, Algenabi et al (2020) revealed that the FTO rs17817449 T allele negatively affects the markers of glycemic control and dyslipidemia in an Iraqi population.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, some FTO associations had lower GGT values, thus indicating a protective role in liver enzyme concentrations. These included GG homozygosity which is a risk factor for obesity (Barseem et al, 2019;Hinney et al, 2007;Jawad & Rasool, 2019;Scuteri et al, 2007) and T2DM development (Hubacek et al, 2018. We are also aware of only one study which associated risk with the T allele. Therein, Algenabi et al (2020) revealed that the FTO rs17817449 T allele negatively affects the markers of glycemic control and dyslipidemia in an Iraqi population.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of environmental factors, like a sedentary lifestyle and excessive nutrient supply, has a large contribution to the end result, more attention should be paid to other relevant obesity-related factors [ 4 ]. Many studies, also in the pediatric population, focus on single nucleotide polymorphisms (SNPs) in genes with a well-described relationship with obesity, such as FTO [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], or genes, whose role in obesity is recently gradually being discovered, as the PLAG1 gene [ 16 , 17 , 18 ]. However, very few studies address the impact of epigenetics, including the DNA methylation of CpG dinucleotides, on this phenomenon [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some research revealed association between FTO rs17817449 and parameters related to metabolic syndrome and type 2 diabetes such as BMI, fasting glucose, fasting insulin, and insulin resistance thus directly increasing the risk of type 2 diabetes development. Such observations were reported in popula-tions of Egypt, the UK, France, Canada, and European Americans [18,19]. In the Czech population the GG genotype of FTO variant rs17817449 was significantly more frequent in individuals with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 53%